Plasticy of close packed long-range ordered Cu-Zn-Al shape memory alloys - Ahlers, Manfred Hermann; Cuniberti, A.; Romero, R. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Ahlers, Manfred Hermann. Comisión Nacional de Energía Atómica; Argentina